2016
DOI: 10.18632/oncotarget.7928
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of the selective toll-like receptor 7 agonist DSR-29133 leads to anti-tumor efficacy in murine solid tumor models which can be potentiated by combination with fractionated radiotherapy

Abstract: Strategies to augment anti-cancer immune responses have recently demonstrated therapeutic utility. To date clinical success has been achieved through targeting co-inhibitory checkpoints such as CTLA-4, PD-1, and PD-L1. However, approaches that target co-activatory pathways are also being actively being developed. Here we report that the novel TLR7-selective agonist DSR-29133 is well tolerated in mice and leads to acute immune activation. Administration of DSR-29133 leads to the induction of IFNα/γ, IP-10, TNFα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, with further optimization, it is possible that immune-based therapies could provide effective tumor responses without the same degree of systemic toxicity as cytotoxic chemotherapy. Several recent studies highlight the dual potential for benefit and harm of TLR7 agonists, which hold substantial promise as anti-tumor agents but cause acute toxicities [34][35][36] . Indeed, we observed that treatment induction was associated with acute hypophagia, weight loss, and decreased locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, with further optimization, it is possible that immune-based therapies could provide effective tumor responses without the same degree of systemic toxicity as cytotoxic chemotherapy. Several recent studies highlight the dual potential for benefit and harm of TLR7 agonists, which hold substantial promise as anti-tumor agents but cause acute toxicities [34][35][36] . Indeed, we observed that treatment induction was associated with acute hypophagia, weight loss, and decreased locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combinations of MEDI9197 with standard of care treatments for cancer, such as chemotherapy and radiotherapy, that drive release of tumor antigens are attractive given the observed vaccine adjuvant activity of MEDI9197 [22, 4143]. Indeed, TLR7 agonists have previously been reported to enhance efficacy in combination with radiotherapy and chemotherapy in syngeneic mouse tumor models [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the efficacy of DSR-29133 was significantly improved when administered in combination with low-dose fractionated radiotherapy. Long-term surviving mice originally treated with DSR-29133 and radiotherapy were protected by a tumor-specific memory immune response which could prevent tumor growth [120]. [121].…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%